Quantitative analysis of shadow x-ray magnetic circular dichroism photoemission electron microscopy - Jamet, S.; Da Col, S.; Rougemaille, N.; Wartelle, A.; Locatelli, Andrea; Mentes, T. O.; Burgos, B. Santos; Afid, R.; Cagnon, L.; Bochmann, Sebastian; Bachmann, Julien; Fruchart, O.; et al. (Physical Review B, 2015)
Shadow x-ray magnetic circular dichroism photoemission electron microscopy is a recent technique, in which the photon intensity in the shadow of an object lying on a surface may be used to gather information about the three-dimensional magnetization texture inside the object. Our purpose here is to lay the basis of a quantitative analysis of this technique. We first discuss the principle and implementation of a method to simulate the contrast expected from an arbitrary micromagnetic state. Textbook examples and successful comparison with experiments are then given. Instrumental settings are finally discussed, having an impact on the contrast and spatial resolution: photon energy, microscope extraction voltage and plane of focus, microscope background level, electric-field related distortion of three-dimensional objects, Fresnel diffraction, or photon scattering.